AN ANALYSIS ON COMPLIMENT RESPONSE STRATEGIES USED BY THE THIRD SEMESTER STUDENTS OF ENGLISH STUDY PROGRAM UNIVERSITAS RIAU - Yuri Oktavia; Indah Tri Purwanti; Dahnilsyah Dahnilsyah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: The purpose of this qualitative descriptive research was to identify the strategies of compliment responses to the EFL learners of the English Study Program of Universitas Riau. This study applied the theory of Holmes (1988) and Farenkia (2012) as supporting idea to analyzethe types of compliment responses. The participants of this research involved 32 EFL participants of the English Study Program selected by using cluster random sampling technique. The instrument of the data was collected by using a DCT (Discourse Completion Task) which contained several situations in which participants were required to response to a compliments. The result showed that the participants used many kinds of strategies in response to a compliment. The accept strategy was the most used by the participants to interact in their daily life. Furthermore, the single appreciation token strategy appeared the most within overall strategies that appeared in the DCT.Key Words: Compliment, Compliment Responses, Types Of Compliment Responses,Speech Act